Lymphostatin, a virulence factor of attaching and effacing Escherichia coli, inhibits proliferation and cytokine responses of human T cells in a manner associated with cell cycle arrest but not apoptosis or necrosis - Ruamsap, Nattaya; Riyapa, Donporn; Janesomboon, Sujintana; Stevens, Joanne M.; Pichyangkul, Sathit; Pattanapanyasat, Kovit; Demons, Samandra T.; Stevens, Mark P.; Korbsrisate, Sunee (Frontiers in Cellular and Infection Microbiology, 2022)
Lymphostatin is a virulence factor of enteropathogenic E. coli (EPEC) and non-O157 serogroup enterohaemorrhagic E. coli. Previous studies using whole-cell lysates of EPEC showed that lymphostatin inhibits the mitogen-activated proliferation of bulk human peripheral blood mononuclear cells (PBMCs) and the production of cytokines IL-2, IL-4, IL-5, and IFN-γ. Here, we used highly purified lymphostatin and PBMC-derived T cells to show that lymphostatin inhibits anti-CD3/anti-CD28-activated proliferation of human CD4+ and CD8+ T cells and blocks the synthesis of IL-2, IL-4, IL-10 and IFN-γ without affecting cell viability and in a manner dependent on an N-terminal DTD glycosyltransferase motif. Such inhibition was not observed with T cells activated by phorbol 12-myristate 13-acetate and ionomycin, implying that lymphostatin targets T cell receptor signaling. Analysis of the expression of CD69 indicated that lymphostatin suppresses T cell activation at an early stage and no impacts on apoptosis or necrosis were observed. Flow cytometric analysis of the DNA content of lymphostatin-treated CD4+ and CD8+ T cells showed a concentration- and DTD-dependent accumulation of the cells in the G0/G1 phase of the cell cycle, and corresponding reduction of the percentage of cells in S phase. Consistent with this, we found a marked reduction in the abundance of cyclins D3, E and A and loss of phosphorylated Rb over time in activated T cells from 8 donors treated with lymphostatin. Moreover, the cyclin-dependent kinase (cdk) inhibitor p27kip1, which inhibits progression of the cell cycle at G1 by acting on cyclin E-cdk2 or cyclin D-cdk4 complexes, was found to be accumulated in lymphostatin-treated T cells. Analysis of the abundance of phosphorylated kinases involved in signal transduction found that 30 of 39 were reduced in abundance following lymphostatin treatment of T cells from 5 donors, albeit not significantly so. Our data provide novel insights into the mode of action of lymphostatin on human T lymphocytes.